Cigarette Smoking in Men and Women and Electronic Cigarette Smoking in Men are Associated with Higher Risk of Elevated Cadmium Level in the Blood - Lee, Jae-woo; Kim, Yeseul; Kim, Yonghwan; Yoo, HyoSun; Kang, Hee-Taik (Journal of Korean medical science, 2020)
We investigated the association between blood concentration of cadmium and smoking status including use of electronic cigarettes (E-cigars). We used data from the Korea National Health and Nutritional Survey 2013 and 2016. A total of 4,744 participants (2,162 men and 2,582 women) were included and were categorized into five groups (Non-smokers, E-cigar non-users in past-smokers, E-cigar users in past-smokers, E-cigar non-users in cigarette-smokers and E-cigar users in cigarette-smokers). Cadmium blood concentration was categorized into tertiles. All sampling and weight variables were stratified, and analysis to account for the complex sampling design was conducted. In both genders, the geometric cadmium concentration was significantly different according to smoking status (both genders, analysis of variance value < 0.001). In men, E-cigar users were significantly higher than the non-smokers ( value = past-smokers, 0.017; cigarette-smokers, < 0.001) when fully adjusted. Compared with non-smokers, fully-adjusted odds ratios (95% confidence intervals) for the highest cadmium tertiles of E-cigar non-users in cigarette-smokers and E-cigar users in cigarette-smokers were 6.56 (3.55-12.11) and 5.68 (1.96-16.50) in men and 2.74 (1.42-5.29) and 1.29 (0.10-17.44) in women. Conventional cigarette smoking in men and women and E-cigar use in men are associated with higher risk of elevated blood cadmium level. Preventive management of cadmium exposure monitoring in conventional cigarette-smokers and E-cigar users may be needed.